The Application of Good Corporate Governance in Adopting Disclosure Policy and Requirements (Journal of Governance and Development (JGD), 2016)
The downfall of corporate structure are based on many reasons including inability to control board members, poor effective control internally, bad managerial decisions and wrong information disclosing to shareholders, investors as well as stakeholders. Moreover poor corporate governance, lack of transparency and inadequate financial reporting system has been reported as the causes of the East Asian financial crisis in 1997. For that reason this paper intent to analyse and discuss the application of good corporate governance amongst Malaysian Public Listed Companies (PLCs) in adopting disclosure policy and requirements. This is a qualitative research involving 38 consumer products of PLCs (i.e. representing 30% out of 126 companies). These companies were chosen as unit analysis using a random probability sampling technique. Content analysis was employed to investigate the practices of good corporate governance amongst consumer products companies listed in Bursa Malaysia. All relevant data/information of PLCs were gathered from the Annual Report of the 38 companies from the period of 2013-2015. The findings of this research show that the PLCs had applied the principle of good governance with adherence to disclosure policy and requirements as required by the Malaysian Code of Corporate Governance and Bursa Malaysia Listing Requirements.